Homogeneous nucleation in water in microfluidic channels - Ando, Keita (2013)
It has been an experimental challenge to test the rupture of liquids with homogeneous nucleation of vapor bubbles. Many prior studies suffered from the ubiquitous presence of impurities in liquids or at container surfaces that spontaneously nucleate and grow under tension. Here, we propose a microfluidic approach to eliminate such impurities and obtain homogeneous bubble nucleation. We stretch the liquid dynamically via the interaction between a laser-induced shock and an air-liquid interface in a microchannel. Reproducible observations of the nucleation of vapor bubbles are obtained, supporting our claim of homogeneous nucleation. From comparisons of the distribution of vapor cavities with Euler flow simulations, the nucleation threshold for water at room temperature is predicted to be -60  MPa.